Informal employment in Ukraine: 2007 survey application - Oksana Nezhyvenko (Наукові записки НаУКМА: Економічні науки, 2016)
Informal employment became a serious challenge for the Ukrainian economy during its adjustment to market conditions. Trends of the number of workers participating in the informal sector have been rising for the last years. The research presents the current state of informal employment in Ukraine. Detailed attention is paid to labour distribution across different population categories. We examine labour market of Ukraine using the data of Ukrainian Longitudinal Monitoring Survey for the year 2007.